2001
DOI: 10.1126/science.1063486
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the TCR to Integrin Activation by SLAP-130/Fyb

Abstract: SLAP-130/Fyb (SLP-76-associated phosphoprotein or Fyn-binding protein; also known as Fyb/Slap) is a hematopoietic-specific adapter, which associates with and modulates function of SH2-containing leukocyte phosphoprotein of 76 kilodaltons (SLP-76). T cells from mice lacking SLAP-130/Fyb show markedly impaired proliferation following CD3 engagement. In addition, the T cell receptor (TCR) in SLAP-130/Fyb mutant cells fails to enhance integrin-dependent adhesion. Although TCR-induced actin polymerization is normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
338
4
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(365 citation statements)
references
References 25 publications
19
338
4
4
Order By: Relevance
“…Furthermore, agonists that directly stimulate integrin activity were able to induce increased adhesion, suggesting that hematopoietic cells from this patient express structurally intact integrins. A constitutively enhanced clustering of the LFA-1 integrin on T cells from this patient was also noted and is particularly interesting in light of in vitro studies suggesting a critical role for LFA-1 clustering in T cell receptor-mediated activation of LFA-1 (6,7,11,12).…”
supporting
confidence: 53%
“…Furthermore, agonists that directly stimulate integrin activity were able to induce increased adhesion, suggesting that hematopoietic cells from this patient express structurally intact integrins. A constitutively enhanced clustering of the LFA-1 integrin on T cells from this patient was also noted and is particularly interesting in light of in vitro studies suggesting a critical role for LFA-1 clustering in T cell receptor-mediated activation of LFA-1 (6,7,11,12).…”
supporting
confidence: 53%
“…However, the Cri1 candidate interval can also be considered to contain genes with a known function in the innate immune system such as the complement component 9 (C9; 6.4 Mb) or the scavenger receptor Enpp2 (54.7 Mb). It also overlaps the FYNbinding protein (Fyb; 6.5 Mb) for which deficient mice display reduced T-cell proliferation 27 as well as the interleukin 7 receptor (Il7r; 9.4 Mb), known to be an important regulator of B-and T-cell proliferation/ differentiation. 28 Although the Il7r gene seems relatively far proximal of the peak linkage region of the Cri1 locus, it is an intriguing candidate as B-cell function has been found to be essential for C. rodentium infection survival.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a role for SLP-76 in integrin activation has been limited to its association with ADAP, inasmuch as prevention of SLP-76/ADAP binding inhibits conjugate formation, which has been shown to be an integrin-mediated event [33]. ADAP itself has been directly linked to integrin activation, as ADAP -/-T cells do not adhere to fibronectin, ICAM, or VCAM following TCR ligation [31,32]. One model for how a SLP-76/ ADAP association may lead to integrin activation is through Src kinase-associated phosphoprotein of 55 kDa, an adaptor that is constitutively associated with ADAP [52] and has been linked to TCR-induced integrin activation [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Its exact role and the molecular mechanism for SLP-76-dependent integrin activation, however, are unclear. Recent data have shown that ADAP, a protein known to be involved in integrin activation [31,32], requires association with SLP-76 via the SLP-76 SH2 domain to mediate enhanced integrin-dependent T cell/ APC conjugate formation and adhesion to ICAM-1 (a b2 ligand) upon overexpression in Jurkat cells [31]. Complementing this finding, overexpression of the SH2 domain of SLP-76 blocks conjugate formation [33].…”
Section: Introductionmentioning
confidence: 90%